1994
DOI: 10.1006/cbir.1994.1025
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor 1α is a component of the subcortical actin bundles of characean algae.

Abstract: Antibodies to elongation factor 1 alpha (EF1 alpha), a known 50 kDa actin-bundling protein in Dictyostelium, identified a protein in a whole cell extract of the characean alga Nitella pseudoflabellata that had an apparent molecular weight of 51 kDa. Indirect immunofluorescence microscopy revealed labelling by the EF1 alpha antibodies of the subcortical actin bundles, even after the motile organelles of the endoplasm were removed by perfusion with ATP-containing solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Consistent with a predicted role of eEF-1A in regulating cytoskeletal structure, in situ studies have shown that eEF-1A is associated with both F-actin (Dharmawardhane et al, 1991;Collings et al, 1994;Clore et al, 1996;Sun et al, 1997) and tubulin (Durso and Cyr, 1994;Durso et al, 1996). Importantly, the distribution of eEF-1A changes when Dictyostelium discoideum.…”
mentioning
confidence: 63%
“…Consistent with a predicted role of eEF-1A in regulating cytoskeletal structure, in situ studies have shown that eEF-1A is associated with both F-actin (Dharmawardhane et al, 1991;Collings et al, 1994;Clore et al, 1996;Sun et al, 1997) and tubulin (Durso and Cyr, 1994;Durso et al, 1996). Importantly, the distribution of eEF-1A changes when Dictyostelium discoideum.…”
mentioning
confidence: 63%
“…In plants, actin filament bundles could be gen- erated in a comparable way. Villins might work coordinately with fimbrins (Kovar et al, 2000), formins (Cheung and Wu, 2004;Favery et al, 2004;Michelot et al, 2005;Ye et al, 2009), LIM proteins (Thomas et al, 2006(Thomas et al, , 2007, and/or elongation factor 1a (Collings et al, 1994) in the formation of thick actin filament bundles. Consistent with this idea, fimbrin has been proposed to cross-link actin filament bundles generated by other actin-bundling proteins, such as villin (Matova et al, 1999;Wu et al, 2010).…”
Section: Vln2 and Vln3 Play A Role In Actin Filament Organization In mentioning
confidence: 99%
“…There are four known families of actin-bundling proteins in plants: villins (Vidali et al, 1998;Klahre et al, 2000;Tominaga et al, 2000;Yokota et al, 2003;Huang et al, 2005;Yokota et al, 2005;Khurana et al, 2010;Zhang et al, 2010), fimbrins (Kovar et al, 2000(Kovar et al, , 2001, formins (Cheung and Wu, 2004;Favery et al, 2004;Michelot et al, 2005;Ye et al, 2009), and LIM proteins (Thomas et al, 2006(Thomas et al, , 2008Wang et al, 2008;Papuga et al, 2010). In addition, elongation factor 1a (Collings et al, 1994;Gungabissoon et al, 2001) has been shown to have actin filament-bundling properties as well. The presence of these different actin-bundling proteins suggests that their combined actions can result in several types of actin filament bundles, which differ in form and function (Thomas et al, 2009).…”
mentioning
confidence: 99%
“…3C). eEF1A is present mainly in the cytoplasm of cells (34), but a small population of eEF1A has been identified previously in the nucleus (35)(36)(37)(38). These two populations of eEF1A may play different physiological roles.…”
Section: Fig 6 Mutation On Sermentioning
confidence: 99%